Mediating Role of Psychological Inflexibility as Transdiagnostic Factor in the Relationship Between Emotional Dysregulation and Sleep Problems With Symptoms of Emotional Disorders - Orouji, Farrin; Abdi, Reza; Chalabianloo, Gholamreza (Frontiers in Psychology, 2022)
This study aims to investigate the mediating role of psychological inflexibility as a transdiagnostic factor in the relationship between emotional dysregulation and sleep problems with symptoms of emotional disorders. A total of 500 subjects from three universities were selected by random multistage clustering, and they completed the Pittsburgh Sleep Quality Index, Difficulties in Emotional Regulation Scale, and Acceptance and Action Questionnaire–II, Inventory of Depression and Anxiety Symptoms. The results of correlation coefficients revealed that there is a positive and significant correlation among emotional dysregulation, sleep problems, and psychological inflexibility with emotional disorders. In addition, the results showed that psychological inflexibility acts as a transdiagnostic factor that mediates the relationship between emotional dysregulation and sleep problems with symptoms of emotional disorders. These findings illustrate how emotional dysregulation and sleep problems affect emotional disorders through psychological inflexibility.